Sleep and Safety Improve Physicians’ Psychological Functioning at Work During Covid-19 Epidemic - Zupancic, Nina; Bucik, Valentin; Ihan, Alojz; Dolenc-Groselj, Leja (Frontiers in Psychology, 2021)
Purpose: The Covid-19 pandemic caused a massive healthcare crisis. To investigate what makes healthcare system resilient and physicians better at coping during a crisis situation, our study investigated the role risk exposure, such as working at Covid-19 entry point, sleep and perceived work safety played in reducing negative psychological functioning at work, as well as their effects on adverse and potentially fatal incidences of compromised safety and medical errors. Methods: Our study included a representative sample of 1189 physicians, from all 12 Slovenian regions and all medical occupations, as registered by the Medical Chamber of Slovenia. For the purposes of this study a Questionnaire of Sleep and Psychological Functioning at Work was developed in the form of an online retrospective self-report. Additionally, our study included items assessing physicians perceived work safety and frequency of negative outcomes (compromised safety and medical errors) during the first month of the Covid-19 epidemic. Results: Physicians working at Covid-19 entry point were more likely to experience night awakening, slept less than 5 hours per night, experience nightmares and had lower levels of psychological functioning in comparison to other physicians. Both hypothesised models showed adequate fit. A higher score on the sleep scale (sleep quantity, sleep quality and shorter sleep latency) has been shown to predict lower levels of negative psychological functioning at work and, indirectly, reduced incidences of compromised safety and medical errors. Contrary to our expectations no significant direct effect of sleep on compromised safety and medical errors was found. When perceived work safety was added into the model, the model showed improved fit, with perceived work safety predicting better sleep, less negative psychological functioning at work and less compromised safety. Conclusion: Sleep and safety both play an important role in ensuring physicians’ psychological functioning at work, decreasing negative and potentially fatal incidents, such as compromised safety and medical errors. Further, research is needed to see how medical guidelines can be updated to ensure physicians sleep and that their safety is protected.